Building interdisciplinary/intersectoral research partnerships for community-based mental health research with older minority adults. - Schensul, Jean J; Robison, Julie; Reyes, Carmen; Radda, Kim; Gaztambide, Sonia; Disch, William (American journal of community psychology, 2006)
Community-based research often brings investigators from different disciplinary backgrounds together with community representatives to conduct research on topics of mutual concern. This paper describes a case example that illustrates an interdisciplinary/intersectoral study of depression and barriers to mental health care among older adults and illustrate the factors central to implementing a successful research partnership. It will address the following conditions that facilitate and challenge interdisciplinary/intersectoral research: (1) achieving commonality of purpose in study design and research and referral approaches; (2) ensuring the ability to develop, field-test and implement psychometrically rigorous and culturally and qualitatively appropriate instruments; (3) building effective management structures for interdisciplinary/intersectoral research partnerships; and (4) identifying, training and supporting qualified researchers to carry out a mental health study with older ethnically diverse adults. The paper concludes with strengths and limitations of the approach.
Keywords: Anthropology, Cultural; Community Mental Health Services; Connecticut; Consumer Participation; Cooperative Behavior; Depression; Health Services Accessibility; Health Services Research; Humans; Interdisciplinary Communication; Mental Disorders; Middle Aged; Minority Groups; Organizational Case Studies; Psychology, Social